STRUCTURAL AND FUNCTIONAL ANALYSIS OF INTERMODAL SCHEME OF PASSES OIL THROUGH THE REPUBLIC OF AZERBAIJAN - Bahirov, S. M.; Hasratova, L. M. (Science and Transport Progress, 2009)
In the article the structural-and-functional analysis of railway-see route Beyneu (Nebit-dag) – Aktau Turkmenbashi) – Djubendi – Poti (Batumi) – Illichivs’k (Varna) has been considered. Also the intermodal scheme of material stream of oil products has created, the analysis of technical development of Djubendi junction has been presented, and its new scheme that allows accelerating the loading operations has been offered.